2021
DOI: 10.1016/j.dsx.2021.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of new-onset diabetic ketoacidosis in patients with moderate to severe COVID-19 receiving parenteral glucocorticoids: A prospective single-centre study among Indian type 2 diabetes patients

Abstract: Background and aim COVID-19 infection predisposes to diabetic ketoacidosis(DKA); whether glucocorticoids enhances this risk is unknown. We aimed to study the occurrence of DKA after initiating glucocorticoids in patients with type 2 diabetes mellitus(T2DM) and moderate-to-severe COVID-19, and identify predictors for it. Methods Patients with T2DM and moderate or severe COVID-19 infection were prospectively observed for development of new-onset DKA for on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Since glucocorticosteroids are used as an effective anti-inflammatory drug in severe COVID-19, it has been discussed receiving corticosteroids in diabetic patients can precipitate the progression of DKA. This study also proposed that the IL-6 level at admission could be a predictive factor for the development of DKA in COVID-19 (Mondal et al 2021).…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 75%
“…Since glucocorticosteroids are used as an effective anti-inflammatory drug in severe COVID-19, it has been discussed receiving corticosteroids in diabetic patients can precipitate the progression of DKA. This study also proposed that the IL-6 level at admission could be a predictive factor for the development of DKA in COVID-19 (Mondal et al 2021).…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 75%
“…Among the included studies, 11 reported DKA and COVID-19 in children [ 8 , 11 , 22 , 30 , 34 , 44 , 45 , 56 , 61 , 66 , 72 ], 56 reported DKA and COVID-19 in adults [ 9 , 10 , 12 21 , 23 , 25 29 , 31 33 , 35 43 , 46 55 , 57 – 60 , 62 65 , 67 71 , 73 75 ], and only 1 study reported DKA and COVID-19 in both children and adults [ 24 ]. There were 54 case report [ 8 12 , 14 , 16 , 17 , 19 23 , 25 27 , 29 42 , 44 51 , 53 58 , 60 , 61 , 64 , 66 , 67 , 69 , 71 , 72 , 74 , 75 ], 10 case series [ 13 , 15 , 28 , 43 , 58 , 59 , 62 , 63 , 70 , 73 ...…”
Section: Resultsmentioning
confidence: 99%
“…This concern has certainly been a factor in the poor overall results of steroid therapy in other viral conditions unless effective anti-viral therapy is given in conjunction. In addition, there is a valid concern supported by anecdotal experience that these individuals may suffer the well-established adverse effects of high dose steroid therapy, including a significant increased risk of new-onset diabetic ketoacidosis (34). New therapies are required in this HI5-NEWS2 low risk group to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%